Case Report and Review of the Literature: Fatal Reversible Cerebral Vasoconstriction Syndrome - Breville, Gautier; Bailly, Amelie; Fisch, Loraine; Kulcsar, Zsolt; Pugin, Deborah; Carrera, Emmanuel (Frontiers in Neurology, 2021)
Background A fatal outcome occurs in 2% of patients with Reversible Cerebral Vasoconstriction Syndrome (RCVS). Due to its rarity, guidelines for the management of the most severe forms of RCVS are lacking. Case presentation Here, we describe the case of a 55 year-old woman who died from complications of Reversible Cerebral Vasoconstriction Syndrome and reviewed patients with fatal outcome reported in the literature. In our patient, the episodes of neurological deterioration could be predicted by elevation of cerebral blood flow velocities assessed with transcranial Doppler. A fatal evolution could not be prevented despite therapeutic escalation consisting of multiple non-invasive and invasive treatments including cervical sympathetic bloc and continuous arterial infusion of nimodipine at the site of severe vasoconstriction. Conclusion This case and the review of literature illustrate the challenges in the management of patients with severe RCVS. We describe here how monitoring of cerebral blood flow can help anticipate clinical worsening and propose novel invasive and non-invasive therapeutic strategies based on monitoring of neurophysiological parameters.